Efektivitas Pembelajaran Bahasa Arab melalui Lagu Anggota Tubuh untuk Anak Usia Dini di RA Ibnu Halim - Hilda Zahra Lubis; Fatimah Nayla Zaskia Siregar; Widya Sari Nasution; Zahra Afifah (Hadlonah: Jurnal Pendidikan dan Pengasuhan Anak, 2024)
This research discusses the effectiveness of learning Arabic through body parts songs for early childhood. The location of this research is RA Ibnu Halim. This type of research uses qualitative methods, the data collection procedures used in this research are questionnaires, observation, interviews, documentation. The aim of this research is to introduce body parts in Arabic to children through body parts songs.